FACTORS AFFECTING THE CAPITAL STRUCTURE OF COMMERCIAL BANKS REGISTERED IN THE STOCK EXCHANGE OF THAILAND - Janwagornwong, Noppawit; Pongsupatt, Apichat (Journal of Buddhist Education and Research (JBER), 2023)
The purpose of this study was to study Factors affecting the capital structure of commercial banks registered in the stock exchange of Thailand. Using 11 Banks for the total period 10 year, from quarter1 year 2012 to quarter4 year 2021. quarter amounted 40 quarters. The independent variable that is used to represent the capital structure is leverage (LEV). The study comprises the factors such as debt service coverage rate (DSCR), firm’s growth (GROWTH), firm’s size (SIZE), non-debt tax shield (NDTS), profitability (PROF) and tangibility (TANG). The study employs panel least squares and fixed effect regression model (FEM) in the capital structure in the banking sector. The result shows that independent variables affecting the capital structure of commercial banks registered in the stock exchange of Thailand, with statistical significance at the level of 0.05 with the R-Squared equal to 0.9328. Firm’s size (SIZE), non-debt tax shield (NDTS), tangibility (TANG) are positively associated with leverage at the significant lever of 0.05. While profitability (PROF) are negatively associated with leverage at the significant level of 0.05. Moreover, debt service coverage ratio (DSCR) and firm’s growth (GROWTH) are not associated with leverage at the significant level of 0.05.